RAS oncogene signal strength regulates matrisomal gene expression and tumorigenicity of mouse keratinocytes. (28th October 2022) - Cataisson, Christophe; Lee, Alex J; Zhang, Ashley M; Mizes, Alicia; Korkmaz, Serena; Carofino, Brandi L; Meyer, Thomas J; Michalowski, Aleksandra M; Li, Luowei; Yuspa, Stuart H
Abstract: Environmental and molecular carcinogenesis are linked by the discovery that chemical carcinogen induced-mutations in the Hras or Kras genes drives tumor development in mouse skin. Importantly, enhanced expression or allele amplification of the mutant Ras gene contributes to selection of initiated cells, tumor persistence, and progression. To explore the consequences of Ras oncogene signal strength, primary keratinocytes were isolated and cultured from the LSL-Hras G12D and LSL-Kras G12D C57BL/6J mouse models and the mutant allele was activated by adeno-Cre recombinase. Keratinocytes expressing one (H) or two (HH) mutant alleles of Hras G12D, one Kras G12D allele (K), or one of each (HK) were studied. All combinations of activated Ras alleles stimulated proliferation and drove transformation marker expression, but only HH and HK formed tumors. HH, HK, and K sustained long-term keratinocyte growth in vitro, while H and WT could not. RNA-Seq yielded two distinct gene expression profiles; HH, HK, and K formed one cluster while H clustered with WT. Weak MAPK activation was seen in H keratinocytes but treatment with a BRAF inhibitor enhanced MAPK signaling and facilitated tumor formation. K keratinocytes became tumorigenic when they were isolated from mice where the LSL-Kras G12D allele was backcrossed from the C57BL/6 onto the FVB/N background. All tumorigenic keratinocytes but not the non-tumorigenic precursors shared a common remodeling of matrisomal gene expression that is associated with tumor formation. Thus, RAS oncogene signal strength determines cell-autonomous changes in initiated cells that are critical for their tumor-forming potential. Abstract : Tumor forming potential of H or K-ras transformed mouse keratinocytes was determined by oncogene dosage, modifying signal strength of the Raf pathway or by cells from a susceptible genetic background. These conditions correlated with the expression of matrisomal genes. Graphical abstract: